Populist Language in the Political Linguistic Landscape of the 2024 Regional Election Campaign in Central Java - Slamet Setiawan; Widyastuti Widyastuti; Eko Satriyo Hermawan; Khazaila Zaini; Wiyaka Wiyaka; Nanik Setyawati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Populist language is increasingly employed in political communication, not only thru speeches and digital media but also in visual campaign media displayed in public spaces. This phenomenon indicates that public spaces have become arenas for the construction of political identity, the legitimation of power, and the representation of local culture. However, studies on populist language within the political linguistic landscape, particularly in visual campaign media in Central Java, remain limited. This study aims to describe the forms of populist language, identify political language strategies, and explain cultural representations in the political linguistic landscape of the 2024 regional election campaign in Central Java. This study employs a descriptive-interpretative qualitative approach based on the perspectives of linguistic landscape, populism theory, and critical discourse analysis. The data consist of 39 campaign texts purposively selected from 150 visual campaign media documented across eleven regencies and municipalities in Central Java. Data were collected thru observation and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that populist language is realized thru the use of local languages, short slogans, repetition, religious diction, popular expressions, development narratives, and populist programs closely related to the needs of local communities. The identified political language strategies include political branding, local and religious legitimation, electoral mobilization, moral imaging, and the promotion of concrete programs, while cultural representations reflect a combination of Javanese cultural values, religiosity, social solidarity, and modern orientation. This study concludes that campaign language in Central Java localizes political legitimacy thru cultural proximity, religious identity, and modern communication styles. The findings contribute to the development of language education and political literacy by enhancing understanding of the relationship between language, culture, ideology, and political communication in public spaces.